Experimental study on the pullout characteristics of toothed warp knitted geogrid in different sand fillers - Yawei, Fu; Wei, Fang (Frontiers in Materials, 2023)
In order to investigate the pullout characteristics of toothed geogrid, the commercialized warp knitted geogrid was combined with the rigid angle aluminum to form the qualified denti-geogrid and used to perform pullout model tests in which four different gradations of fillers, three denti-strip heights, as well as three normal stress levels were adopted. The research shows that: (1) At the initial stage of pullout test, the pullout resistance rises rapidly, and only the curves of pullout force (T) and pullout displacement (△L) under lower normal stress peaks. The maximum pullout resistance is positively related to normal stress on the model, the denti-strip height, and the coarse particle content. (2) As the denti-strip height increases, the coefficient of reinforcing effect, the quasi shear strength parameters and the quasi friction coefficient all show enhancements to some extent, as well as the drawing coefficient. When the normal stress rises, the quasi shear strength parameters both increase, while the quasi friction coefficients gradually decrease. The quasi shear strength parameters and the quasi friction coefficient are positively correlated with the coarse particle content, while the drawing coefficient has a negative correlation with the coarse grain proportion. (3) It could be inferred that the denti-strip with suitable height and coarser gradation of the filler would be beneficial to enhance the anti-pullout performance in reinforcement project entities, and the bearing resistance acting on the denti-strip is able to play a more dominant role in low-backfill condition. The research results can furtherly enrich the relevant achievements in the field of spatial reinforcement, and provide useful evidence for the design and construction of related projects, especially for low embankment filling.